Islamic Counseling Guidance Program to Prevent Social Media Addiction (Research at SMA Kartika Bandung) - Succy Ayu Pertiwi; Lilis Satriah; Hajir Tajiri (al-Afkar, Journal For Islamic Studies, 2024)
Excessive use of social media is a phenomenon that is increasingly worrying among teenagers, not only affecting students' mental and physical health, but also having a negative impact on academic achievement and social interaction. This research also wants to implement an Islamic counseling guidance program at Kartika Bandung High School. This type of research uses a qualitative approach with a case study method. Data collection techniques use interview, observation and documentation techniques. The informants in this research were guidance and counseling teachers, students and school principals. The results of the research show that (1) the Islamic Counseling Guidance Program at SMA Kartika Bandung is implemented in accordance with the school's vision and mission, namely creating a religious generation to help students overcome challenges and provide guidelines for living according to Islamic teachings. (2) The implementation of the BKI Program is carried out through various methods such as group counseling with an Islamic approach and self-management techniques. (3) The effective results of the BKI Program can be seen from increased student awareness, changes in behavior and habits, increased skills in managing social media, support from the school environment and family (4) The formulation of this Islamic guidance and counseling program is designed to help students at SMA Kartika XIX-1 Bandung manage their use of social media in a way that is in accordance with Islamic teachings, with the aim of reducing students dependence on social media through an Islamic approach that emphasizes spiritual, moral and social values.